(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze factors associated with very preterm and extremely preterm birth among preterm infants at Thai Nguyen Central Hospital. Methods: A cross-sectional descriptive study was conducted on 110 preterm infants (<37 weeks of gestation) at the Pediatric Center, Thai Nguyen Central Hospital. Results: Maternal age ≥35 years, educational level at or below high school, and occupations such as farmers/workers were significantly associated with an increased risk of very preterm and extremely preterm birth (<32 weeks) (p < 0.05). Obstetric factors including ≤1 pregnancy, assisted conception, history of preterm birth, history of miscarriage/induced abortion, and maternal medical history were also significantly associated with very preterm and extremely preterm birth (p < 0.05). Conclusion: Very preterm and extremely preterm birth are significantly associated with multiple maternal and obstetric risk factors. These findings highlight the importance of screening, monitoring, and management of high-risk pregnancies.